Effect of aggregate size and superficial horizon differentiation on the friability index of soils cultivated with sugar cane: a multivariate approach (2015)
Soil friability is a physical property that provides valuable information for minimizing energy consumption during soil tillage and for preparing the edaphic medium for plant development. Its quantitative determination is generally carried out with aggregates obtained from soil blocks taken at fixed depths of profiles without considering the superficial horizons of the soil. The objective of the this study was to determine the effect of aggregate size and superficial horizon differentiation on the friability index (FI) of some soils cultivated with sugar cane in the Geographic Valley of the Cauca River (Colombia), using univariate (CVu) and multivariate (CVm) coefficients of variation. The FI was evaluated using a compression test with four aggregate-size ranges taken from the Ap and A1 superficial horizons of 182 sampling sites located on 18 sugar cane farms. Of the five types of studied soils (Inceptisols, Mollisols, Vertisols, Alfisols and Ultisols), 7,280 aggregates were collected that were air dried and subsequently dried in a low-temperature oven before determining the tensile strength (TS), which was in turn used to calculate the FI using the coefficient of variation method. This study found that the FI varied with the aggregate size and the soil depth (first two horizons). Only three of the four size ranges initially selected were relevant. The CVm proved to be very useful for the selection of a more relevant value from the confidence interval of the TS from the CVu method for friability and established that the lower limit value (FIi) of the TS CVu was the FI value that was closest to the multivariate measurement.